2017
DOI: 10.1186/s12939-017-0595-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self-perceived health for Canadians aged 40 and older and policy implications

Abstract: BackgroundPerceived health status indicates people’s overall perception of their health, including both physical and psychological dimensions. The aim of this study was to examine the determinants of self-perceived health for Canadians aged 40 and older using data from the Canadian Community Health Survey (2010).MethodsMultiple logistic regression models were employed to identify factors associated with self-perceived health in two age groups: Adults aged 65+ and Adults aged 40–64.ResultsWe found that higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 44 publications
3
51
1
1
Order By: Relevance
“…As expected, age was strongly associated with poor self--perceived health both in the univariate and multivariate analyses. This was in line with a significant number of other studies, although some studies showed no association between age and self-perceived health or even the opposite effect of the age (Bonner et al, 2017;Menec & Nowicki, 2014;Jerez--Roig et al, 2016;Janković & Simić, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As expected, age was strongly associated with poor self--perceived health both in the univariate and multivariate analyses. This was in line with a significant number of other studies, although some studies showed no association between age and self-perceived health or even the opposite effect of the age (Bonner et al, 2017;Menec & Nowicki, 2014;Jerez--Roig et al, 2016;Janković & Simić, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…ISCED 2011 differentiates nine levels of education: level 0 -No formal education or below, level 1 -Primary education, level 2 -Lower secondary education, 3 -Upper secondary education, 4 -Post-secondary but non-tertiary education, 5 -Short-cycle tertiary education; 6 -Bachelor's or equivalent level; 7 -Master's or equivalent level and 8 -Doctoral or equivalent level. Low education level included ISCED 0-2, medium included ISCED 3-4 and high included ISCED 5-8 (Bonner et al, 2017). Education level was determined according to the highest education level completed based on the International Standard Classification of Education-2011 (ISCED-2011).…”
Section: Variablesmentioning
confidence: 99%
“…Level of education was also found to have significant interaction with self-perceived health status towards patient satisfaction where patients with higher education who perceived themselves in better health status expressed a higher level of satisfaction. A study based on the Canadian Community Health Survey of over 20,000 adults found that more educated patients tend to report better health [ 30 ]. As healthier people are less likely to need as much medical care and interact with healthcare providers less frequently, they may have less opportunity to experience problems with access to health care and express more satisfaction with the care received [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…to report better health [30]. As healthier people are less likely to need as much medical care and interact with healthcare providers less frequently, they may have less opportunity to experience problems with access to health care and express more satisfaction with the care received [29].…”
Section: Plos Onementioning
confidence: 99%
“…Self-rated health is a consolidated indicator related to well-being and quality of life [ 10 ]. It is considered a predictor of morbidity, mortality and health services use [ 11 , 12 ] and has been widely used in health and socio-economic surveys at population level in Europe (for instance, in Denmark, Germany, Ireland, Italy, Iceland and Norway) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%